Agos ng dugong kayumanggi isang kasaysayan ng sambayanang Pilipino (Philippine history) - Veneracion, Jaime Balcos 1945- (Manila Abiva Pub. House, 2004)
Interactive CD-ROM on the history of the Filipino community.
This interactive CD-ROM is meant to be a supplement to Dr. Veneracion's book with the same title.
Introduksyon -- Pagpapanahon -- Ang kasaysayan ng Pilipinas -- Dibuho at Larawan -- Mga pagsusulit.
System requirements: Pentium II processor or higher; 128MB RAM; monitor with 800 x 600 display resolution; 24X CD-ROM drive; sound card for audio.
Keywords: Philippines -- History; Philippines -- Politics and government